Coverage Denials for Medical Necessity Rules in Medicare. (15th September 2021) - Schwartz, Aaron; Brennan, Troyen; Jagmin, Christopher; Verbrugge, Dorothea; Newhouse, Joseph
Abstract : Research Objective: Coverage policy may be an important tool to reduce spending while discouraging low‐value medical services. Government and private insurers may also differ in their scope of coverage restrictions for suspected low‐value services. However, basic facts about coverage denials are unknown because denials are not identifiable in standard research datasets. In this study, we characterized fundamental features of coverage denials for medical necessity using data on all claims denied by a large Medicare Advantage health insurer. Study Design: We analyzed medical benefit claims for Medicare Advantage beneficiaries. We detected all claims that were denied for failing to meet medical necessity rules. Some rules were made by the government (i.e. national or local coverage determinations) and other rules were made by the private insurer. We measured the frequency of denials, associated spending, affected service types and provider specialties, the reasons for denials, and temporal trends in denials. We also quantified differences between denials due to government coverage rules and denials due to private insurer coverage rules. Population Studied: We analyzed 2014–2019 claims for all Medicare Advantage beneficiaries enrolled with the health insurer Aetna. Our sample included 2.9 million unique beneficiaries (mean age = 73, 56% female, 5% Medicaid dual eligible). Principal Findings: There were 0.84 denials per beneficiary per year (95% CI 0.83–0.84), corresponding to 1.45% of claims (95% CI 1.44–0.46), with 31.8% of beneficiaries affected each year (95% CI 31.8–31.9). Denied claims accounted for 64 per beneficiary per year (95% CI 63–65), or 0.73% of medical spending (95% CI 0.71–0.76). Denial rates increased over time, from 0.59% of spending in 2014 to 0.85% of spending in 2019 (p < 0.01). Government coverage rules accounted for 83% of denied claims, but only 60% of denied spending, and private insurer coverage rules accounted for the remaining denials. Most services denied under private insurer coverage rules were categorized as experimental/investigational (49%), not a treatment for disease (20%), or without proven efficacy (16%); denials for services categorized as cosmetic were rare (1%). A large majority of claims denied under Medicare coverage rules were for laboratory tests (75%), most of which were for chemistry studies. Denials under private insurer coverage rules were more widely distributed across service types; home care and chemotherapy accounted for the greatest shares of denied spending (14% and 11%). The provider types with the greatest share of denied spending were hospital outpatient departments (34%) and laboratories (19%). Conclusions: For a large Medicare Advantage insurer, denials under medical necessity rules accounted for a small but growing fraction of annual spending. While most spending was denied under government coverage rules, additional private insurer rules targeted different types of services and accounted for additional denied spending. Implications for Policy or Practice: To the authors' knowledge, this study presents the first comprehensive evidence on how often medical services are denied for failing to meet medical necessity criteria. In Medicare Advantage, coverage denials appear to contribute to modest savings, derived from both government‐produced and private insurer‐produced coverage criteria. Primary Funding Source: NIH, CVS Health, Phyllis & Jerome Rappaport Foundation.